My money my way : taking back control of your financial life - Love, Kumiko (Portfolio / Penguin, 2022)
"As a newly divorced single mom making $24,000 per year and facing down $77,000 in debt, Kumiko Love worried constantly about money. She saw what other moms had-vacations, birthday parties, a house full of furniture-and felt ashamed that she and her son lived in a small apartment and ate dinner on the floor. Worse, when her feelings began to exhaust her, she binge-shopped, reasoning that she'd feel better after a trip to the mall. On the day she needed to pay for a McDonald's ice cream cone with her credit card, she had an epiphany: Money is not the problem. Self-Doubt is the problem. Shame is the problem. Guilt is the problem. Society's expectations for her are the problem. She is the solution. Once she reversed the negative thinking patterns pushing her toward decisions that didn't serve her values or goals, her financial plan wrote itself. Now, she's not only living debt-free in her dream home, which she paid for in cash, but she has spread her teachings around the world and helped countless women envision better lives for themselves and their families. Building on the lessons she's taught millions as the founder of The Budget Mom, she shares a step by step plan for taking control back over your financial life-regardless of your level of income or your credit card balance. Through stories from navigating divorce to helping clients thrive through recessions, depression, eviction, layoffs and so much more, you will learn foundational practices such as: How to use your emotions to your financial advantage, instead of letting them control you; how to create a budget based on your real life, not a life of self-denial; how to create a motivating debt pay-off plan that makes you excited about your future, instead of fearing it. My Money My Way will give you the tools to align your emotional health with your financial health-to let go of deprivation and embrace desire. Love's paradigm-shifting system will teach you how to honor your unique personal values, driving emotions, and particular needs so that you can stop worrying about money and start living a financially fulfilled life"--